Evaluation of the Android-based Learning Outcomes Report for Effective and Effective Student Learning Outcomes - Marwan Efendi; Handaru Jati (Postgraduate, University of Mataram, 2023)
In the implementation of submitting reports on student learning outcomes both daily scores, midterm exam scores, and final semester exam scores still use e-reports. thus causing a lack of interest in student learning because learning outcomes cannot be obtained by students/parents in an updated manner. Parents experience difficulties in knowing their children's learning outcomes because parents only get their children's learning results in the middle of the semester and the end of the semester. Schools also experience difficulties, namely: in archival storage. Related to these conditions, good cooperation is created for the application of the SIHABEL software Android-Based Learning Outcomes Evaluation Report as an information system for reporting learning outcomes so that later the reporting process will run effectively. The method used in this research is R&D (Research and Development) version 4D (Define, Design, Develop, Disseminate). Based on the results of this product test it can be concluded that the SIHABEL software Evaluation of Android-Based Learning Outcomes Reports helps schools in carrying out student learning outcomes reporting effectively and can provide the information needed by stakeholders quickly and validly